Model-building technique of quasisteady operations of water supply network with leaks - Тевяшев, А.Д.; Козыренко, С.И.; Непочатова, В.Д. (Eastern-European Journal of Enterprise Technologies, 2010)
In this paper we consider a stochastic model of a quasistationary flow distribution in engineering networks that most adequately describes the modes of their work and is most effective for the formulation and solution of problems of operational planning regimes of engineering networks.